2012
DOI: 10.3343/alm.2012.32.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Single-color Multitarget Flow Cytometry Using Monoclonal Antibodies Labeled with Different Intensities of the Same Fluorochrome

Abstract: BackgroundWe developed a single-color multitarget flow cytometry (SM-FC) assay, a single-tube assay with graded mean fluorescence intensities (MFIs). We evaluated the repeatability of SM-FC, and its correlation with multicolor flow cytometry (MFC), to assess its application as a routine FC assay.MethodsWe selected CD19, CD3, CD4, and CD8 as antigen targets to analyze a lymphocyte subset. MFIs were graded by adjusting monoclonal antibody (mAb) volumes to detect several cell populations. Dimly labeled mAb was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…For instance, the number of lymphocytes averaged approximately 1,000/ml of blood (see Table 2), which is within the range of 490-6,000/ml (median of 2,000/ml) as reported by Park and Han (2012). The percentages of CD3þ lymphocytes (*80%), CD16þ/CD56þ cells (*10%), and CD19þ cells (*10%) were also in line with other reports (Abud-Mendoza et al, 2012; Carlson, Speca, Faris , & Patel, 2007;Park & Han, 2012). Regarding the ratio of Th1 to Th2 cells, others have reported ratios from 12.5 (Toldi et al, 2011) to 5.1 (Cseh et al, 2012), while we observed ratios ranging from 3.4 to 9.1 in the present study, depending upon the group.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, the number of lymphocytes averaged approximately 1,000/ml of blood (see Table 2), which is within the range of 490-6,000/ml (median of 2,000/ml) as reported by Park and Han (2012). The percentages of CD3þ lymphocytes (*80%), CD16þ/CD56þ cells (*10%), and CD19þ cells (*10%) were also in line with other reports (Abud-Mendoza et al, 2012; Carlson, Speca, Faris , & Patel, 2007;Park & Han, 2012). Regarding the ratio of Th1 to Th2 cells, others have reported ratios from 12.5 (Toldi et al, 2011) to 5.1 (Cseh et al, 2012), while we observed ratios ranging from 3.4 to 9.1 in the present study, depending upon the group.…”
Section: Resultssupporting
confidence: 91%
“…Also, the baseline biomarker levels we obtained in the present study are similar to those other researchers have reported for similar populations. For instance, the number of lymphocytes averaged approximately 1,000/μl of blood (see Table 2), which is within the range of 490–6,000/μl (median of 2,000/μl) as reported by Park and Han (2012). The percentages of CD3+ lymphocytes (~80%), CD16+/CD56+ cells (~10%), and CD19+ cells (~10%) were also in line with other reports (Abud-Mendoza et al, 2012; Carlson, Speca, Faris, & Patel, 2007; Park & Han, 2012).…”
Section: Resultssupporting
confidence: 89%
“…Other reports have successfully combined few markers in two fluorochrome to positively identify and separate immune cell populations. [ 16 18 ]. Combining multiple antibodies in single channels is an accepted methodology that has also been implemented in clinical standardized protocols to identify malignant leukocytes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are indicated as TF1-antiCD4 and TF2-antiCD19 MAbs. [26][27][28] Thiophene fluorophores provide MAbs with attractive features for spectroscopic characterization. 28,29 First, the platforms were incubated with each single TF-labeled antibody at pH 5.0, to ensure that the proteins would be loaded via ion exchange mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-human CD4 and CD19 monoclonal antibodies (MAbs) were chosen for the detection of T and B lymphocytes, respectively. 27,28 These selected monoclonal antibodies were previously labeled with thiophene fluorophores (TFs). TFs are fluorescent probes characterized by high optical stability, bright fluorescence, and large Stokes shifts, particularly well-suited for multiplexing analyses.…”
Section: Introductionmentioning
confidence: 99%